Warner Bros : the making of an American movie studio - Thomson, David, 1941- (New Haven : Yale University Press, 2017)
Behind the scenes at the legendary Warner Brothers film studio, where four immigrant brothers transformed themselves into the moguls and masters of American fantasy Warner Bros charts the rise of an unpromising film studio from its shaky beginnings in the early twentieth century through its ascent to the pinnacle of Hollywood influence and popularity. The Warner Brothers-- Harry, Albert, Sam, and Jack-- arrived in America as unschooled Jewish immigrants, yet they founded a studio that became the smartest, toughest, and most radical in all of Hollywood. David Thomson provides fascinating and original interpretations of Warner Brothers pictures from the pioneering talkie The Jazz Singer through black-and-white musicals, gangster movies, and such dramatic romances as Casablanca, East of Eden, and Bonnie and Clyde. He recounts the storied exploits of the studio's larger-than-life stars, among them Al Jolson, James Cagney, Bette Davis, Errol Flynn, Humphrey Bogart, James Dean, Doris Day, and Bugs Bunny. The Warner brothers' cultural impact was so profound, Thomson writes, that their studio became "one of the enterprises that helped us see there might be an American dream out there."
An introduction: families and stories -- The greatest moment? -- What are brothers for? -- Family dinner -- Mustache -- For liberty? -- Rinty -- Mama, darlin' -- Now -- My forgotten man -- Be somebody -- Bette v. Everyone -- Contracts and company -- Unafraid? -- Bogart -- After the war, before the end -- Jacob's ladder.
Includes bibliographical references (pages 193-204) and index.
Keywords: Warner Bros. Pictures (1923-1967) -- History; Warner Bros. Pictures (1923-1967) -- Historia; Motion picture studios -- California -- Los Angeles -- History; Motion picture producers and directors -- United States -- Biography; Estudios cinematográficos -- Historia -- Los Angeles -- California; Productores y directores de cine -- Estados Unidos